Ovarian structure protein 1: A sensitive molecular biomarker of gonadal intersex in female Japanese medaka after androgen exposure - Abdel-Moneim, Ahmed; Mahapatra, Cecon T; Hatef, Azadeh; Sepúlveda, Maria S (Environmental toxicology and chemistry, 2015)
Intersex in gonochoristic fish can be induced after exposure to androgens and estrogens. The main objective of the present study was to identify biomarkers that would be predictive of intersex in Japanese medaka (Oryzias latipes) after exposure to synthetic hormones. First a gene was identified, ovarian structure protein 1 (osp1), with strong female-specific expression during gonadal differentiation. The authors hypothesized that osp1 expression would decrease to male levels in females after the exposure of larvae (15-25 d postfertilization [dpf]) to 17β-trenbolone (TRB; 5 ng/L) and would increase to female levels in males exposed to 17α-ethinylestradiol (EE2; 5 ng/L) and that gonadal intersex would be induced later in life (60 dpf). Tissue distribution and cellular localization of OSP1 was investigated using Western blot and immunohistochemistry. The results indicate that this exposure regime delays testicular maturation in males and development of ovarian intersex in females. Although decreased osp1 expression in females exposed to TRB correlated to changes in ovarian phenotype, up-regulation of osp1 was not observed in males exposed to EE2. In addition, OSP1 was only observed in ovaries and localized in the cytoplasm and follicular layer of immature and mature oocytes. The authors conclude that osp1 is a promising biomarker of androgen exposure and gonadal intersex in female medaka.
Keywords: Endocrine Disruptors; Animals; ovarium; Oryzias; Female; Androgens; Ethinyl Estradiol; biologické markery; Intersex; poruchy sexuálního vývoje; Biomarkers; Gene Expression Regulation, Developmental; ženské pohlaví; Japanese medaka; endokrinní disruptory; Immunohistochemistry; Gonads; gonády; trenbolon; Trenbolone Acetate; imunohistochemie; rybí proteiny; Male; Fish Proteins; Estrogenic compounds; Endocrine-disrupting compounds; Disorders of Sex Development; Larva; zvířata; mužské pohlaví; vývojová regulace genové exprese; ethinylestradiol; Ovary; larva